Mid-to-long-term outcomes of the frozen elephant trunk procedure in aortic pathology: a systematic review and meta-analysis - Eranki, Aditya; Downes, David; Muston, Benjamin; Debs, Connor; Tyagi, Daksh; Munir, Liam; Wilson-Smith, Ashley R.; Gupta, Aashray (Annals of Cardiothoracic Surgery; Vol 14, No 5 (September 30, 2025): Evolution of Elephant Trunk II, 2025)
Background: The frozen elephant trunk (FET) provides single-stage repair of complex, concomitant aortic arch and descending aortic disease, integrating both conventional and endovascular approaches. While multiple meta-analyses affirm short-term safety, long-term outcomes remain largely unknown, especially regarding overall survival and freedom from re-intervention. This current systematic review and meta-analysis aims to summarize the short- and long-term outcomes following the use of FET in aortic pathology. Methods: Studies with at least two years of follow-up data on FETs were identified in five electronic databases, which were searched from inception of records until July 2025. The primary outcome of interest was mortality, with short-term data presented as either 30-day or in-hospital mortality, and long-term data as aggregated Kaplan-Meier curves. Subgroup analysis was also compared by etiology. Secondary outcomes included relevant morbidity outcomes. Results: Following independent screening, 28 studies were included for analysis, with 11,292 patients and a mean follow-up period of 40.4 months. Actuarial overall survival at 1, 5 and 10 years was 86.2%, 78.8% and 67.9%, respectively. Long-term survival for acute dissection for these points was marginally higher, at 86.2%, 82.4%, and 75.2%, respectively. Overall freedom from distal reintervention at 1, 5, and 10 years was 93.9%, 87.4% and 81.5%, respectively. Comparatively, pooled short-term mortality was marginally higher in the aortic dissection cohort than the overall cohort at 7.7% [95% confidence interval (CI): 6–11%] and 7% (95% CI: 5–9%), respectively. The breakdown for these was 254/3,379 and 742/9,428 patients, respectively. For the overall cohort, postoperative spinal cord injury (SCI), postoperative cerebrovascular accident (CVA), and acute renal failure (ARF) requiring dialysis were 4%, 8% and 11%, respectively. Pooled mean intensive care unit (ICU) length of stay was 7 days. A high level of heterogeneity was present, likely due to the mixed etiologies included. Conclusions: Our long-term data expands on previous literature while affirming similar favorable long-term survival for the FET procedure. The consistent pattern of improved late-survival in acute dissections supports the hypothesis that early false-lumen exclusion and acute remodeling result in clear long-term benefits. The need for re-intervention has remained consistent with the published literature, further highlighting the importance of patient selection.